Association of FOXE3-p.Ala170Ala and PITX3-p.Ile95Ile polymorphisms with congenital cataract and microphthalmia - Nair Gopinathan Vidya; Darshini Ganatra; Abhay R Vasavada; Sankaranarayanan Rajkumar (Journal of Ophthalmic & Vision Research, 2018)
Purpose: To investigate the association of FOXE3-p.Ala170Ala (rs34082359) and PITX3-p.Ile95Ile (rs2281983) polymorphisms with congenital cataract and microphthalmia in a western Indian population. Methods: FOXE3-p.Ala170Ala (c.510C>T) and PITX3-p.Ile95Ile (c.285C>T) polymorphisms were genotyped in 561 subjects consisting of 242 cases with congenital cataract, 52 with microphthalmia, and 267 controls using polymerase chain reaction-restriction fragment length polymorphism. Approximately 10% of samples were randomly sequenced for each single nucleotide polymorphism to confirm the genotypes. The prediction of mRNA secondary structure for polymorphism FOXE3-p.Ala170Ala and PITX3-p.Ile95Ile was performed. Results: A significantly high frequency of T allele and a borderline significance in the frequency of TT genotype of FOXE3-p.Ala170Ala was observed in microphthalmia cases, as compared to controls [T allele: OR: [CI] = 1.8 [1.15-2.72], P = 0.0115; TT: OR [CI] = 2.9 [1.14-7.16], P = 0.0291). The frequency of CC genotype was significantly low in microphthalmia cases when compared to controls (CC: OR [CI] = 0.5 [0.24-0.86, P = 0.0150). There was no significant difference in the allele and genotype frequencies of PITX3-p.Ile95Ile between cases and controls. A slight free energy change was observed in the secondary structure of mRNA between the FOXE3-p.Ala170Ala C-allele (-917.60 kcal/mol) and T-allele (-916.80 kcal/mol) and between PITX3-p.Ile95Ile C-allele (-659.80 kcal/mol) and T-allele (-658.40 kcal/mol). Conclusion: The present findings indicate that FOXE3-p.Ala170Ala 'T' allele and 'TT' genotype could be predisposing factors for microphthalmia while 'CC' genotype might play a protective role against it. A reduction in the free energy change associated with FOXE3-p.Ala170Ala 'T' allele could further contribute towards disease risk.